ANALYSIS OF JOHN FIELD’S PIANO NOCTURNES H.46 AND H.37 - Keleş, Özlem; Sağirkaya, Burak (Tolga Karaca, 2025)
John Field, widely regarded acknowledged as the inventor of the nocturne form, is particularly renowned for his works that paved the way for piano music in the Romantic period. This study examines the significance of J. Field in piano literature through an analysis of his nocturnes H.37 and H.46. Within this scope, the nocturnes are both technically and musically explored, aiming at the same time to contribute fresh insights to the literature. The primary source for this study is the Field Dua Nokturny edition published by Polskie Wydawnictwo Muzyczne (PWM) in 1978. This edition has been identified as a commonly preferred resource among pianists interpreting J. Field’s works and as a widely used reference for accessing his compositions. Despite being extensively performed among J. Field's works, the review found that the nocturnes H.37 and H.46 have not received enough in-depth analysis in the existing literature. In the first part of the study J. Field’s contributions to piano literature are addressed through an overview of his biography. The second part provides a detailed analysis of nocturnes H.37 and H.46. Through this analysis process, both the thematic and harmonic structures of the works, as well as their technical difficulties and periodic features, have been tried to be revealed under a single source. The findings presented in this study are expected to serve as a valuable resource for pianists and theorists. Furthermore this research is anticipated to shed light on future studies in this field. Each new examination into J. Field’s works is foreseen to deepen contemporary understanding of the music in the Romantic period. © 2025, Tolga Karaca. All rights reserved.
JOHN FIELD’IN H. 46 VE H. 37 PİYANO NOKTÜRNLERİNİN ANALİZİ
Keywords: John Field; musicalanalysis; nocturne; piano; romanticism in music